Embedded Isoreticular Zeolites: Concept and Beyond. Issue 63 (22nd September 2017) - Cho, Jung; Choi, Hyun June; Guo, Peng; Shin, Jiho; Zou, Xiaodong; Hong, Suk Bong
Abstract: Invited for the cover of this issue are the groups of Xiadong Zou at the Stockholm University and Suk Bong Hong at the POSTECH in Pohang. The image depicts a zeolite family with expanding structural complexity and embedded isoreticular structures. Read the full text of the article at 10.1002/chem.201702417 . Abstract : " The prediction and synthesis of new crystal structures enables the targeted preparation of materials with desired properties ." Read more about the story behind the cover in the Cover Profile and about the research itself on page 15922 ff. (DOI:10.1002/chem.201702417 ).